Penentuan pH Optimum Komposit Silika dari Abu Sekam Padi dengan Arang Aktif untuk Menurunkan Kadar Fosfat - Djabar Gzalib; Dahlan Dahlan; La Harimu (PKimia FKIP Universitas Halu Oleo, 2021)
Research has been carried out with the title Study on the Use of Silica Composites from Rice Husk Ash and Activater Carbon to Reduce Phospate Levels. This Study aims to determine the optimum adsorben silica-activated carbon to reduce Phospat levels. The research method used is a quantitative analysis method. The result showed that the composite silica- activated carbon at an optimum pH of 5 with an adsorbtion effeiciency of 69,1 %. Thuse the composite silica-activated carbon can be used as an adsorbent to reduce phospate levels.